REPRESENTASI IDENTITAS DIRI REMAJA KOMUNITAS PUNK DI SALATIGA - Rizal Amrun’adzim; Muhammad Yusuf Arwiarto; Deliyanto (Universitas Muhammadiyah Metro, 2026)
This study aims to analyze the representation of adolescent self-identity within the punk community in Pasar Rejosari, Salatiga City, using Erikson's identity development theory, Marcia's identity status theory, Tajfel's social identity theory, and Mead's symbolic interactionism as the analytical framework. This research employs a qualitative method with an exploratory approach to understand the subjective experiences of adolescents in constructing and interpreting their identities. Data were collected through in-depth interviews, observation, and documentation involving four informants who are members of the punk community. The findings reveal that adolescent self-identity is represented through three main aspects: physical appearance, social interaction, and self-meaning. Physical appearance such as dark clothing, tattoos, accessories, and distinctive hairstyles serves as symbols of self-expression and freedom, while social interaction fosters solidarity, belonging, and acceptance for marginalized adolescents. Analyzed through Erikson's and Marcia's lenses, the punk community functions as a psychosocial moratorium space in which adolescents explore and consolidate identity commitments, while from Tajfel's perspective, group membership provides a positive social identity and self-esteem amid stigma from out-groups. This study also proposes a conceptual model of adolescent identity formation within the punk community and discusses its implications for guidance and counseling practice, particularly in supporting marginalized youth and fostering positive self-concept.